Text and Interpretation : New Approaches in the Criticism of the New Testament - Petzer,; Hartin, (New Testament Tools, Studies and Documents ;, 1991)
Text and Interpretation gives an insight into the many different approaches that more recent South African scholarship has adopted in the interpretation of the New Testament. While the number of approaches in New Testament interpretation has proliferated over the past few years, all the proposals still fall under one of the three traditional poles: sender (author) - text - receptor (reader). Classified according to this division each chapter has a twofold aim. Firstly, the perspective is situated within a wider framework of interpretation to illustrate the context out of which this approach emerges. Secondly, each article has selected a particular New Testament text to demonstrate this approach in practice. The authors of these chapters - the majority of which are South African scholars - were chosen because of their expertise in their specific fields. By presenting these studies together in one collection, the scholarship in these different areas will become more readily accessible to a wider group of scholars.